Stress management training program to address caregiver burden and perceived stress among family caregivers of patients undergoing hemodialysis: a randomized controlled trial study - Ramisa Khouban-Shargh; Seyedmohammad Mirhosseini; Saeed Ghasempour; Mohammad Hasan Basirinezhad; Ali Abbasi (BMC Nephrology, 2024)
Abstract Background The objective of the current study was to assess the effectiveness of stress management training, grounded in Lazarus and Folkman’s stress management model, on reducing caregiving burden and perceived stress among family caregivers of patients on hemodialysis. Methods This two-group clinical trial study was conducted in parallel design among 60 family caregivers of patients on hemodialysis in 2023. The participants were divided into two groups of training and control using a random quadruple block allocation method. The intervention took place over two months, in six online group sessions of 35–45 min. Zarit Burden Inventory (ZBI) and Cohen’s Perceived Stress Scale (PSS-14) were used to collect information before and two weeks after the intervention. The study data were analyzed using and analysis of covariance (ANCOVA), pair, and independent t-tests at a significance level of 0.05. Results At baseline, the two groups exhibited homogeneity in terms of mean scores for caregiving burden (Training group = 50.8 ± 4.9; Control group = 49.1 ± 6.0; P = 0.264) and perceived stress (Training group = 32.8 ± 4.7; Control group = 31.5 ± 2.4; P = 0.192). Nevertheless, following the intervention, there was a significant decrease in caregiving burden (Training group = 45.9 ± 4.1; Control group = 49.0 ± 5.8; P = 0.017) and perceived stress (Training group = 28.0 ± 4.4; Control group = 30.7 ± 3.5; P = 0.01) scores within the training group compared to the control group. Conclusion Based on the findings of the current study, given that family caregivers of patients on hemodialysis encounter psychological distress and contend with the negative aspects of care, it is advisable to implement psycho-educational interventions, such as stress management training. Incorporating these interventions into the care plan for hemodialysis could help mitigate these adverse consequences and provide valuable support for family caregivers. Trial registration Iranian Registry of Clinical Trials (IRCT), IRCT20180728040617N6. Registered on 17/04/2023.